Oral Health Condition and Nutritional Status among Cleft Lip and Palate in Baghdad-Iraq - Almaeeni, Mais M; Hassan, Abeer M (Journal of Baghdad College of Dentistry, 2017)
Background: Orofacial cleft is the most common craniofacial birth defect and the fourth most common congenital malformation in humans that have an effect on oral health in addition to nutrient intake affected in those children. This research aims to investigate gingival condition, dental caries experience and nutritional status among children with orofacial cleft and compare them with normal children. Materials and methods: The study group included 36 children with an age ranged (4-9) years of orofacial cleft. The control group included 37 children matched the control group in age and gender. Gingival condition measured by Gingival Index (Löe and Silness, 1963), while dental caries status was measured by (D1-4MFs/d1-4mfs) index according to the criteria of Manji et al (1989). The nutritional status was assessed using body mass index for age. Data analysis was conducted through the application of the SPSS (version 21). Results: The DMFs, dmfs and Ds mean values were higher in study group than control group with no statistically significant differences, while ds mean values were higher in study group than control group with highly significant difference. GI mean values were higher in study group than control group with statistically highly significant difference. No significant difference in body mass index between study and control groups. Concerning severity, the study group had more gingival inflammation severity than control group, while regarding dental cries severity only grades d1, d3 and d4 were significantly increased in study group than control group. Conclusion: The children with orofacial clefts had increased risk for dental caries and gingival inflammation than normal children. The nutritional status was not different between children with orofacial cleft and healthy children